Strategy Of Omni Channel Marketing & Business Sustainability Of E Commerce Through The Character And Mindset Of Msmes During The Covid-19 Pandemic In Siantar City - Arif Lubis; Bongsu Hutagalung3; Andrew Satria Lubis4; Doli Muhammad Ja’far Dalimunthe (TALENTA Publisher, Universitas Sumatera Utara, 2023)
This study examines UMKM’s strategy to survive the COVID-19 pandemic. The findings of this study can help UMKM actors make decisions during pandemic uncertainty. This study is slightly different from previous, similar studies. Previous research looked at the long-term viability of UMKM businesses and competition among UMKM. However, during the COVID-19 pandemic, the situation was very different. This is not separate from the market anomalies that absorb UMKM products. UMKM faces the most difficult time in its business history. This investigation explains a change in the behavior of both UMKM perpetrators and buyers in the face of a pandemic. The research also shows that the surviving UMKM business operators are those who are able to adapt and innovate in their services and production processes. This research is expected to contribute to the development of UMKM strategies to survive the Covid-19 pandemic.